Turning Trash into Blessings: EcoBrick Impact Analysis Workshop for Teenagers at Miftakhul Huda Mosque, Balikpapan - Pontoh, Arief Nugraha; Syaputra, Eko Agung; Arifuddin, Andi Mursid Nugraha (PT FORMOSA CENDEKIA GLOBAL, 2024)
The EcoBrick program, a collaboration between Remaja Masjid Miftakhul Huda in Balikpapan and the Kalimantan Institute of Technology (ITK), aims to reduce plastic waste through training on converting waste into alternative building materials. The program includes socialization, theoretical training, production practices, discussions, and exhibitions. Evaluations using pre-tests and post-tests show significant improvements in participants' understanding, skills, and awareness of waste management. This program empowers communities while providing innovative solutions for reducing plastic waste. Consequently, EcoBrick has market potential as an eco-friendly product, enhancing environmental quality.